Layanan Informasi Tentang Strategi Penangangan Dan Pencegahan Bulying Di Pondok Pesantren Darul Qur’an - Asmidaryani, Asmidaryani; Habibah, Ummy; Syawitri, Melsy; Tampubolon, Sintong; Elmirawati, Elmirawati (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2024)
Recently, we have been shocked again by the increasing phenomenon of bullying, both carried out in the community and in the school environment, where it seems that the perpetrators are enjoying their actions, as evidenced by the recording process which looks as if the conditions have been well planned. Without them Realize that bullying behavior can have short-term and long-term impacts, especially for victims of bullying. The most serious risk is if this bullying behavior happens to children, because they will be more at risk of experiencing various health problems, both physical and mental, such as anxiety, depression which may be difficult to forget until they grow up. What is even more worrying is that it is not uncommon for those who initially If you are a victim, one day you can become a perpetrator, so it has a chain effect that is difficult to break. This service aims to explore and present the implementation of information services regarding strategies for handling and preventing bullying at the Darul Qur'an Islamic Boarding School. This community service activity uses lecture, discussion and question and answer methods. The approach is carried out by looking for/exploring participants' problems and providing solutions. The activity started with a lecture on important things related to bullying, types of bullying, the impact and how to deal with it if bullying occurs around you, plus a video showing related to bullying education. Participants' problems were identified during the question and answer process